Prohibisi Homoseksual dalam Al-Qur’an: Studi Analisis Tafsir Maqāṣidī - A, Muh. Nasruddin; Junaid, Junaid bin (JOURNAL OF QUR'AN AND HADITH STUDIES, 2023)
Homosexuality is one type of human sexual orientation that the mufasirs have prohibited such behavior as has been done by the people of Prophet Luth. The view of the mufasirs in the prohibition leads that homosexual behavior violates the nature of human creation which lives in pairs between men and women. So in this study using the theory of maqāṣidī interpretation approach, researchers will prove that the relationship between men and women is a more maqāṣidī-ah and healthy relationship, besides that this research will also reveal the purpose and wisdom of the prohibition of homosexual behavior. So the results of this study can be concluded that the wisdom of the prohibition of homosexuality contains several maqāṣid, namely hifẓ al-nasl (continuing generations), hifẓ al-dīn (continuing and fighting for the teachings of Islam), hifẓ al'aql (avoiding excessive attitudes) and hifẓ al-nafs (avoiding disease). Homosexual behavior will not provide benefits for life but rather provide harm.